PENGEMBANGAN E-MODUL UNTUK PEMBELAJARAN DIFERENSIASI PADA MATERI PERANGKAT KERAS KOMPUTER KELAS VII SMP - Rafi Septrianda; Ulfia Rahmi; Eldarni, Reni Kurnia (STKIP Subang, 2025)
This Development Research was motivated by a problem at SMPN 27 Padang, namely that students were limited to the material presented by teachers through workbooks and printed books that were monotonous because they only contained black and white text without visualizations or interactive activities. This condition had an impact on low student motivation and learning outcomes, while teachers also had difficulty accommodating differentiated learning. This study aims to develop an e-module on computer hardware material that can be used in differentiated learning for seventh grade junior high school students. The Research method used is Research and Development (R&D) with the 4D model (Define, Design, Develop, Disseminate). Data collection instruments include material validation, media validation, teacher and student practicality questionnaires, as well as pre-test and post-test questions. The results showed that the average material validation by experts was 98.09%, media validation by expert I was 97.64%, and media validation by expert II was 94.11%, all of which were categorized as highly valid. Teacher practicality obtained a percentage of 97.39% and student practicality was 94.73%, both of which were categorized as highly practical. The effectiveness test produced an average N-Gain of 0.70, categorized as quite effective. Thus, the developed e-module is suitable for use as a differentiated learning medium for computer hardware material in seventh grade junior high school.